Skuteczność polskiej administracji podatkowej - Kluzek, Marta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Economists highly appraised effectiveness of Polish tax administration in previous decade in comparison to other countries in transition economies. But now the transformation process is slower in our country. Polish tax administration has been criticized by taxpayers and the Ministry of Finance. Thus many things should be changed in administration functioning in order to improve of its effectiveness and for this reason administration's reform is necessary as soon as possible. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 180-190